The impact of educational and computer programs on improving the educational outcomes of kindergarten students in the first Zarqa Education Directorate in Jordan - Abu Saleh, Belal Saleh (Journal of Educational and Psychological Sciences, 2019)
The study aimed at identifying the impact of educational software and computer on improving the educational outcomes of kindergarten students in Zarqa first Directorate. The study population consisted of all kindergarten students in the first Zarqa Education Directorate. The purposive sample of the study was on the students of Al-Wessam kindergarten (41) students, where the researcher used the semi-experimental method. The researcher reached a set of results, most notably are, to improve the performance of students on the application of software prepared by the researcher was a high degree. In light of the results, the researcher recommended to circulate this software to all kindergarten students in the Directorate of Zarqa I.
Keywords: educational software; educational outcomes; kindergarten